Odpowiedzi

2009-12-03T15:56:52+01:00
3/4 * 6/7= 9/14
3/5 - 2/4=1/10
1/3 + 2/7=13/21

3x * (-5) + 7 * (-2 + x) = 3x
-15x-14+7x=3x
-11x=14
x=-14/11

0= 6x - 6
6x=6
x=1
1 4 1
2009-12-03T15:59:24+01:00
3/4*6/7=9/14
3/5-2/4=1/10
1/3+2/7=13/21
3x * (-5) + 7 * (-2 + x) = 3x
-15x-14+7x=3x
-11x=14
x=-14/11

0= 6x - 6
6x=6
x=1
powinno być dobrze
1 1 1
2009-12-03T16:00:33+01:00
A)
3/4 * 6/7=18/28=9/14
b)
3/5 - 2/4=12/20 - 10/20=2/20=1/10
c)
1/3 + 2/7=7/21 + 6/21 =13/21
d)
3x * (-5) + 7 * (-2 + x) = 3x
-15x-14+7x=3x
-8x-3x=14
-11x=14 /:(-11)
x=-14/11


0= 6x - 6
-6x=-6 /:(-6)
x=1
1 5 1